Spin decoherence processes in the S = 1/2 scalene triangular cluster (Cu3(OH)) - A N Ponomaryov; N Kim; Z H Jang; J van Tol; H-J Koo; J M Law; B J Suh; S Yoon; K Y Choi (New Journal of Physics, 2015)
We report the synthesis and magnetic properties of the molecular cluster Cu _3 ( ${{μ }_{3}}$ −OH)( μ -OH)( μ -O _2 Ar $^{4F-{\rm Ph}}$ ) _2 (py) _3 (OTf) _2 , abbreviated as (Cu _3 (OH)). Using magnetization, electron paramagnetic resonance and spin dimer analysis, we derive a microscopic magnetic model of (Cu _3 (OH)) and measure the electron T _1 and T _2 relaxation times. The Cu ^2+ ions are arranged to form a distorted triangular structure with the three different exchange coupling constants ${J_{1}}=-43.5$ K, ${J_{2}}=-53.0$ K, and ${J_{3}}=-37.7$ K. At T = 1.5 K T _1 is of the order of 10 ^−4 s and T _2 is evaluated to be $0.26\;μ {\rm s}$ . We find that the temperature dependence of $1/{T_{1}}$ and $1/{T_{2}}$ is governed by Orbach process and spin bath fluctuations, respectively. We discuss the role of spin–phonon mechanism in determining a spin decoherence time in a class of spin triangular clusters.